Uncovering EFL students - Asnas, Sania Alinda Mouli; Hidayanti, Ika (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Presently, writing research articles causes anxiety for EFL students because they have to modify their writing to fit the English academic writing style, so academic writing is the most difficult skill to master because it requires an intricate process. Therefore, this study aims to uncover the frequent difficulties of academic writing and the coping strategies faced by EFL students. This study used a mixed method. Fifty-five participants from the English Department at a private university in Malang, Indonesia, filled out the questionnaire, and five participants were interviewed. The quantitative data were analyzed using descriptive statistics, and the qualitative data were analyzed thematically. The results showed that students experienced frequent difficulties, namely structure, developing ideas, vocabulary, and grammar, and the most frequent difficulty was grammar. To overcome challenges in grammar aspects, there were four manual coping strategies that they applied such as reading more articles, looking carefully at the function of conjunction, learning more about spelling, capitalization, and punctuation, and editing their work, and three automatic coping strategies that they used, namely using Grammarly, using an online English monolingual dictionary, and using Microsoft Word. The implications are to assist students in identifying and overcoming their frequent difficulties when writing academically.